2015
DOI: 10.1074/jbc.m115.644583
|View full text |Cite
|
Sign up to set email alerts
|

The Neurexin/N-Ethylmaleimide-sensitive Factor (NSF) Interaction Regulates Short Term Synaptic Depression

Abstract: Background: Neurexins (NRXs) are cell adhesion molecules and regulate synapse formation and synaptic transmission. Results: NRX associates with NSF in vivo, and the absence of NRX/NSF interaction results in abnormal distribution and impaired function of NSF. Conclusion: NRX/NSF interaction facilitates NSF recruitment and subsequent SNARE complex disassembly. Significance: Neurexin regulates the presynaptic exocytotic machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Neurexins function in the formation and transmission of synapses (Dean et al, 2003;Li et al, 2015;Missler et al, 2003;Qiu et al, 2007;Scheiffele, 2003;Zeng et al, 2007) and were also shown to interact directly with neuroligin on the postsynaptic membrane to influence dendrite growth and stability in Xenopus (Chen et al, 2010). In addition, a-neurexin knockout mice exhibit shortened distal dendritic branches (Dudanova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neurexins function in the formation and transmission of synapses (Dean et al, 2003;Li et al, 2015;Missler et al, 2003;Qiu et al, 2007;Scheiffele, 2003;Zeng et al, 2007) and were also shown to interact directly with neuroligin on the postsynaptic membrane to influence dendrite growth and stability in Xenopus (Chen et al, 2010). In addition, a-neurexin knockout mice exhibit shortened distal dendritic branches (Dudanova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neurexins and neuroligins are cell adhesion molecules that function in synapse formation8910 and synaptic transmission1112. Mutations in neurexin and neuroligin genes have been linked to autism1314.…”
mentioning
confidence: 99%
“…Different cell types show different levels of NSF/NSF2 expression (Ordway et al, 1994;Boulianne and Trimble, 1995;Pallanck et al, 1995;Golby et al, 2001;Mohtashami et al, 2001), indicating they have different demands for its function. We detected both genes by qRT-PCR from ovaries, and found high expression levels of NSF protein in the early germline and follicle cells, including polar cells, by antibody staining (Li et al, 2015) (not shown). Next, we overexpressed NSF2 in follicle cells.…”
Section: Introductionmentioning
confidence: 91%
“…The following primary antibodies were used: mouse anti-Eya (10H6, DSHB; 1:100) (Bonini et al, 1993), mouse anti-Armadillo (N27A1, DSHB; 1:40) (Riggleman et al, 1990), rabbit anti-Apt ( provided by S. Hirose, National Institute of Genetics, Mishima, Japan; 1:1000) (Liu et al, 2003), guinea pig anti-Apt from GST-Apt (Pocono Rabbit Farm, 1:5000), rat anti-Slbo ( provided by P. Rorth, Institute of Molecular and Cell Biology A-STAR, Proteos, Singapore; 1:1000) (Beccari et al, 2002), anti-rabbit GFP (Life Technologies; 1:250), rat anti-Drosophila E-Cad (DCAD2, DSHB;1:20) (Oda et al, 1997), rat anti-human influenza hemagglutinin (HA) (11867423001, Roche; at 0.5 µg/ml), mouse anti-FasIII (7G10, DSHB;1:50) (Patel et al, 1987), rabbit anti-NSF ( provided by J. Han, Southeast University, Nanjing, China; 1:50; Li et al, 2015) and α-Snap ( provided by L. Pallanck, University of Washington, Seattle, WA; 1:600; Babcock et al, 2004). Images were acquired with a Carl Zeiss AxioImager Z1 and Apotome optical sectioning with Axiovision acquisition software.…”
Section: Immunofluorescence Labeling and Phenotypic Analysismentioning
confidence: 99%
See 1 more Smart Citation